2018
DOI: 10.1371/journal.pone.0203352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body habitus on contrast-induced acute kidney injury after percutaneous coronary intervention

Abstract: BackgroundLimiting the contrast volume to creatinine clearance (V/CrCl) ratio is crucial for preventing contrast-induced acute kidney injury (CI-AKI) after percutaneous coronary intervention (PCI). However, the incidence of CI-AKI and the distribution of V/CrCl ratios may vary according to patient body habitus.ObjectiveWe aimed to identify the clinical factors predicting CI-AKI in patients with different body mass indexes (BMIs).MethodsWe evaluated 8782 consecutive patients undergoing PCI and who were register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Due to an inverse relation between inflamation and albumin, low albumin levels in CIN patients might be explained by increased inflamation status. The relation between BMI and CIN development has been evaluated in different studies and the results are confounding [1][2][3][4] . Some studies have shown that low BMI, while others have established that a high BMI is a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to an inverse relation between inflamation and albumin, low albumin levels in CIN patients might be explained by increased inflamation status. The relation between BMI and CIN development has been evaluated in different studies and the results are confounding [1][2][3][4] . Some studies have shown that low BMI, while others have established that a high BMI is a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-induced nephropathy (CIN) is a commonly observed undesirable condition in patients undergoing percutaneous coronary intervention (PCI). CIN is related with poorer outcomes for patients, including need for renal dialysis and higher mortality [1][2][3] . Previous studies reported that the prevalence of CIN after CAG or PCI procedures range from 2%-15% and can reach up to 50% in patients under high risk such as diabetes mellitus (DM) and pre-procedural renal failure 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations